Exploring the mechanisms of Qingdu Fang for the treatment of cervical HR-HPV using UPLC-QTOF-MS, network pharmacology, and cell experimentation - Wang, Shanyun; Li, Guangru; Wang, Zhuqiang; Luo, Qing; Zeng, Jianfeng; Xiao, Jing (Frontiers in Pharmacology, 2024)
Background: Qingdu Fang (QDF) is a traditional Chinese herbal formula with remarkable clinical effect in the treatment of HR-HPV, but its mechanism remains unclear. In this study, UPLC-QTOF-MS was used to detect its components, network pharmacology was used to explore the traditional Chinese medicine monomers and their related targets for the treatment of HR-HPV in QDF. Molecular docking and in vitro experiments were performed to verify the results. Methods: QDF constituents and active compounds were identified using UPLC-QTOF-MS analysis. TCMSP and GeneCard databases were used to identify active components, targets, and potential therapeutic targets in HR-HPV. PPI network was constructed using the String database to analyze protein-protein interactions. Cytoscape3.7.2 was used to construct PPI networks, while GO enrichment and KEGG pathway analyses with R. The effect of QDF on H8 cell proliferation was measured using the CCK-8 method, and apoptosis and cell cycle was assessed with flow cytometry. The effects of QDF on PI3K/AKT pathway were detected by Western blotting. Results: A total of 27 compounds were identified on QDF by UPLC-QTOF-MS. Base on Network pharmacology,a total of 254 target genes are involved in the action of QDF on cervical HR-HPV. PPI analysis suggested that TP53, JUN, AKT1, STAT3, TNF and IL6 were potential targets for QDF treatment of HR-HPV. Molecular docking shows that two compounds have strong binding activity with AKT1. CCK-8 and morphological observation have shown that QDF inhibits H8 cell proliferation in a dose-dependent manner. Flow cytometry experiments suggest that QDF induces apoptosis and cell cycle arrest in H8 cells. Western blotting experiments reveal that QDF inhibits the PI3K/AKT signaling pathway. Conclusion: QDF has a multi-faceted therapeutic approach for HR-HPV, targeting inflammation, oxidation, and apoptosis. It induces apoptosis in H8 cells by inhibiting the PI3K/AKT pathway.